THE VALUE OF COMPETENCE-BASED APPROACH IN THE PREPARATION OF DENTAL HYGIENISTS - V.M. Kosenko (Український стоматологічний альманах)
The relevance of the study: Rapid development of prophylactic direction in dental science, use of information and communication technologies in all areas of life require not only the formation of certain knowledge and skills in students, including dental hygienists, but also common (universal) and specific (professional) competences.